2023
DOI: 10.1039/d3tb00281k
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic assembly of gold nanoparticle and metal–organic framework nanoparticles attenuates amyloid β aggregate-mediated neurotoxicity

Abstract: The deposition of amyloid β (Aβ) is a conventional pathological hallmark of Alzheimer’s disease (AD). Consequently, the inhibition of Aβ aggregation combined with disaggregation of Aβ fibrils is an important...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Cell viability studies demonstrated no cytotoxicity [294] Engineered gold NPs NPs with a diameter of1-2 nm showed toxicity due to irreversible binding. No toxicity was observed in the case of NPs of the range of3-100 nm [142] Metal oxide NPs (TiO…”
Section: Surface-modified Gold Nps Of Various Sizesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability studies demonstrated no cytotoxicity [294] Engineered gold NPs NPs with a diameter of1-2 nm showed toxicity due to irreversible binding. No toxicity was observed in the case of NPs of the range of3-100 nm [142] Metal oxide NPs (TiO…”
Section: Surface-modified Gold Nps Of Various Sizesmentioning
confidence: 99%
“…• Developed PEG-MIL 101-AuNPs demonstrated a marked decline in fibrillation by disrupting Aβ 42 fibrils, thereby decreasing the aggregation[142] …”
mentioning
confidence: 99%